ROLE OF PRINCIPAL IONS OF SEA WATER IN SORPTION OF CU(II) ON 7-ANGSTROM MNO2 - Zaytseva L.V.; Putilina V.S.; Barentsov I.M. (My University, 1987)
The authors report on a more thorough study and test of the conclusion that the nature and concentration of MG2+, K+ and Li cations in chloride solutions affect the sorption of Cu(II) by birnessite (7-angstrom MnO2). To ascertain the roles of the principal components of sea water in the sorption of Cu(II) by birnessite we compared sorption in a solution of LiCl in which the cation, like Na+ and Mg2+, is positively hydrated, and in synthetic sea water. In natural sea water, the effect of the principal ions shows up strikingly if we compare the concentrations of copper or other heavy meals in iron-manganese nodules of different water bodies, i.e., lakes, inland waters and oceans (Atlantic, Indian and Pacific). At depths of about 5 km we should expect increased diffusion of heavy metals (Cu, Ni and the like) in sea water of low viscosity, plus a relatively high structure-breaking effect of the relative abundant negatively hydrated ions. This promotes more active chemisorption accumulation of Cu, Ni, etc. on manganese and iron hydroxides.